Complications of continuous ambulatory peritoneal dialysis: An early experience in tertiary hospital of Western region of Nepal - Maskey, Abhishek; Dhakal, Niraj; Regmi, Chirayu (Journal of Advances in Internal Medicine, 2017)
Background and Aims: Chronic ambulatory peritoneal dialysis (CAPD) has been established form of therapy in adults patients with end stage kidney diseases and has emerged as a feasible modality of renal replacement therapy. The aim of the study was to evaluate the complications of CAPD and its contributing factor in order to improve the patient survival and reduce morbidity and mortality. Methods: A hospital based retrospective study of 35 patients who opted for CAPD at Manipal teaching hospital, Pokhara from 1st June 2015 to 31st May 2016 was carried out. Results: Total 35 CAPD patients were included in study. The mean age of the patients was 45.78±16.34 years. Nineteen (54%) patients were male. The total follow up was 533 patients months with mean follow up of 15.22 ±5.02 months. There were 41 episodes of different complications that occurred during the study period with rate of 0.9 episodes/patient years. There were 18 (43%) episodes of peritonitis including 5 recurrence of peritonitis in 5 patients, 6 (15%) exit site infections, 6 (15%) failure of drainage, 2 (5%) pericatheter leakage, 2 (5%) catheter displacement , 2 (5%) omental wrapping, 2 (5%) catheter removal, 2 (5%) mortality. The commonest pathogen for peritonitis was staphylococcus aureus in 5 (22%) episodes. Conclusion: Overall complications rate was comparable to other studies. Peritonitis rate has been declined in our study. The majority of non-infectious complications are treatable and do not interfere with the catheter survival. CAPD is a safe and viable mode of renal replacement therapy alternative to hemodialysis. Journal of Advances in Internal Medicine Vol.5(2) 2016: 34-37